Associations Between Classification Criteria Items in Systemic Lupus Erythematosus. Issue 12 (7th November 2020) - Touma, Zahi; Cervera, Ricard; Brinks, Ralph; Lorenzoni, Valentina; Tani, Chiara; Hoyer, Bimba F.; Costenbader, Karen H.; Sebastiani, Gian Domenico; Navarra, Sandra V.; Bonfa, Eloisa; Ramsey‐Goldman, Rosalind; Tedeschi, Sara K.; et al.
Abstract : Objective: A project aimed at developing new classification criteria for systemic lupus erythematosus (SLE) is based on weighted criteria that include both laboratory and clinical items. Combinations of certain symptoms may occur commonly in SLE, which provides an argument against independently counting these items. The current study was undertaken to evaluate the interrelationship between candidate criteria items in the International Early SLE cohort and in the Euro‐Lupus cohort. Methods: The International Early SLE cohort included 389 patients, who were diagnosed within 3 years prior to the study. Data on the ACR's 1997 update of the SLE revised criteria, the Systemic Lupus International Collaborating Clinics 2012 criteria, and on 30 additional items were collected. To evaluate the interrelationship of the criteria, a tetrachoric correlation was used to assess the degree of association between different manifestations in the same organ system. The correlations identified in the International Early SLE cohort were validated in the Euro‐Lupus cohort. Results: A few relevant correlations were observed among specific clinical cutaneous manifestations (in particular, malar rash correlated with photosensitivity, alopecia, and oral ulcers) and serologic manifestations (anti‐Sm and anti–double‐stranded DNA and anti–RNA polymerase, anti‐Ro and anti‐La, and antiphospholipid antibodies), and these results were validated in the Euro‐Lupus cohort. The associations within the mucocutaneous domain, hematologic and the specific autoantibodies suggest that within a single domain only the highest ranking item should be counted to avoid overrepresentation. Conclusion: Some of the candidate SLE criteria cluster within domains. Given these interrelationships, multiple criteria within a domain should not be independently counted. These results are important to consider for the structure of new SLE classification criteria.